Development of high order thinking skills in Indonesian teachers - J. Surjanti; A. F. Prakoso; R. Y. Kurniawan; N. C. Sakti; E. I. Nurlaili (Russian State Vocational Pedagogical University, 2022)
Introduction. The 21st century teachers need be able to create students who are creative and have critical thinking skills which are possibly obtained by implementing high order thinking skills (HOTS) in learning activities.Aim. This study aims to examine whether teacher professional knowledge (TPK) can improve teacher's critical thinking (CT) and whether HOTS literacy (HL) and teacher professional development (TPD) can mediate the relationship between TPK and CT.Methodology and research methods. This study is explanatory research with 724 teachers serves as respondents. The analysis was carried out using WarpPLS and data were collected through questionnaire.Results and scientific novelty. The research results demonstrate that TPK affect CT directly and indirectly. HL and TPD intermediate the relationship of TPK on CT.Practical significance. This study provides important information to relevant stakeholders, such as the Ministry of education, universities, and schools which explains or proposes factors that can improve teachers' ability in developing critical thinking or higher-order thinking based questions. This information needs to be immediately known so stakeholders or policy makers can design appropriate regulations or policy that can develop teacher capacity and education curriculum.